Gunshot injuries to the maxillofacial region: Computed tomographic evaluation in a Southern Nigerian Tertiary Hospital - O Ehimwenma; P E Esezobor (International Journal of Medicine and Health Development, 2013)
Objective: To evaluate Computed Tomographic findings in patients with gunshot injury (GSI) to the maxillofacial region. Materials And Methods: A retrospective cohort study of patients who had Computed Tomography (CT) scanning done for GSI to the maxillofacial region at the University of Benin Teaching Hospital (UBTH), from 2006 to 2013 was undertaken. Serial axial CT slices were taken at 5 and 10mm intervals. Medical Records of the patients with special emphasis on the patient's demographics was sourced from the request forms and CT findings were obtained from CT reports and images. The data was entered into a proforma and analyzed using SPSS version 17. Results: The mean age of subjects was 35.07 ± 15.67 years and males were by far more commonly affected comprising 92.6%. The left side of the face was predominantly affected and this occurred in 16 (59.3%) patients. Facial fractures occurred in majority of the patients (85.2%) with the frontal bone being mostly affected when fractures were assessed in isolation. The most common intracranial complication was hemorrhage in 29.6%. Other complications included intracranial pellet retention, pneumocephalus and cerebral oedema. Conclusion: CT is a valuable tool in the setting of maxillofacial GSI providing accurate spatial localization of bullet pellets and information regarding complications that may arise from such injuries.